Angular Unconformity of the Late Quaternary Strata in the Hetao Basin, North of the Ordos Block (West China): Timing and Its Tectonic Implications - Bai, Luanxi; Xu, Xiwei; Luo, Hao; Li, Kang; Tan, Xibin; Zhao, Junxiang (Frontiers in Earth Science, 2021)
Following the uplift of the Tibet Plateau and the continuous subduction of the Pacific Plate, graben faulting began to appear around the Ordos Block in the Cenozoic. The Hetao Basin is a Cenozoic rift basin between the Ordos Block and the Yinshan Mountains, and Late Quaternary sedimentary strata, which have lacustrine facies, are widely distributed inside this basin. However, the evolution of the Hetao Basin and its related fault systems has been debated for a long time due to the lack of tectonic evidence. In this study, four sections named Haolaigou, Bianqianghao, Huhesala, and Hazigai are selected along the north margin of the Hetao Basin. With the lithology and structural analysis of the Upper Pleistocene series in these sections, two new angular unconformities are found within the 10 m thick sedimentary sequence of the lacustrine sediments. Based on the dating results, we speculate that these two upper and lower angular unconformities are formed between 33 ka BP and 40 ka BP, and 60 ka BP and 80 ka BP, respectively. The angular unconformities also provide tectonic constraints for the latest and ongoing tectonic activity in the Quaternary. This tectonic movement begins at around 80 ka BP and causes two different unconformities of the lower strata with varying degrees of deformation (tilt) but also leads to the final death of the ancient lake.